Fistulas Enterocutaneous - Handling Clinical - Surgical - Borja O., José Luís; Moncayo A., Fernando; Campaña B., Xavier (Revista Universidad de Guayaquil, 2012)
Fistulas find skin have become complications prevalent in patients treated by surgical services of hospitals, mainly after operative approach of the abdomen with direct intervention or not of the gastrointestinal tract, with the consequent morbidity and mortality alarming. Fistulas find skins are a complication of abdominal surgery, although they may occur for other reasonsbut, inflammatory bowel disease. It is a relatively rare, is associated with a morbidity and mortality high, mainly in relation to other complications such as sepsis, and poses a major challenge to surgeons, gastroenterologists and other professionals. The spontaneous closure occurs in 30% of cases, being necessary to resort to surgery when it fails the conservative treatment, which is placed in the first instance. Early diagnosis, initial aggressive support measures clinical stabilization and proper timing of the surgery, if necessary, condition very significantly the prognosis. Malnutrition is common, the traditional form of nutritional support is parenteral nutrition, and although the restriction of oral intake and bowel rest are principles that apply in common form, there is no evidence that this practice will be
Keywords: Fistulas find skin; sepsis